Modeling coupled kinetics of arsenic adsorption/desorption and oxidation in ferrihydrite-Mn(II)/manganese (oxyhydr)oxides systems. (April 2020) - You, Yajie; Liang, Yuzhen; Peng, Shimeng; Lan, Shuai; Lu, Guining; Feng, Xionghan; Shi, Zhenqing
Abstract: The speciation and mobility of As are controlled by both Fe and Mn (oxyhydr)oxides through a series of surface complexation and redox reactions occurring in the environment, which is also complicated by the solution chemistry conditions. However, there is still a lack of quantitative tools for predicting the coupled kinetic processes of As reactions with Fe and Mn (oxyhydr)oxides. In this study, we developed a quantitative model for the coupled kinetics of As adsorption/desorption and oxidation in ferrihydrite-Mn (oxyhydr)oxides and ferrihydrite-Mn(II)–O2 systems. This model also accounted for the variations in solution chemistry conditions and binding site heterogeneity. Our model suggested that Mn (oxyhydr)oxide and ferrihydrite mainly served as an oxidant and an adsorbent, respectively, when they coexisted. Among the three types of binding sites of ferrihydrite, the adsorbed As(V) was mainly distributed on the nonprotonated bidentate sites. Our model quantitatively showed that the oxidation rates of different reaction systems varied significantly. The rates of As(III) oxidation were enhanced with higher pH values and higher molar ratios of Mn(II)/As(III) in the ferrihydrite-Mn(II)–O2 system. This study provides a modeling framework for predicting the kinetic behavior of As when multiple adsorption/desorption and oxidation reactions are coupled in the environment. Highlights: Model was built for coupled adsorption/desorption and oxidation kinetics of As. Ferrihydrite-preformed Mn (oxyhydr)oxides and ferrihydrite-Mn(II) systems were investigated. Model described well variations in concentrations of As species over time. The oxidation rates of the investigated systems were quantified and compared.